2021
DOI: 10.3390/ijerph18073469
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Forest Visit Numbers in Different Regions and Population Segments before and during the COVID-19 Pandemic

Abstract: In view of the prevailing preferences for health and recreation revealed by previous studies as the main expected benefits of forest visits, the research presented herein focuses on whether such expectations would translate into a significant increase in the number of forest visits (NFV) following pandemic outbreaks. In this context, a Slovak nationwide survey on forests was conducted, with the main objective of casting light on possible changes in NFV as a coping mechanism or behavioral response to the discom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 34 publications
3
42
0
Order By: Relevance
“…Given these uncertainties, future qualitative, as well as quantitative, research efforts, such as those used in this study, will be crucial for drawing conclusions about visitor preferences and motivations to visit the forest after the lockdown. The results from a nationwide survey of residents of Slovakia [77] showed that forest accessibility was a paramount factor affecting the number of forest visits in both pre-COVID-19 situations and during the pandemic. In terms of the effects on NFV, settlement size was linked with forest accessibility through distance to the nearest forest, which was lowest in villages and towns with up to several thousand inhabitants.…”
Section: Discussionmentioning
confidence: 99%
“…Given these uncertainties, future qualitative, as well as quantitative, research efforts, such as those used in this study, will be crucial for drawing conclusions about visitor preferences and motivations to visit the forest after the lockdown. The results from a nationwide survey of residents of Slovakia [77] showed that forest accessibility was a paramount factor affecting the number of forest visits in both pre-COVID-19 situations and during the pandemic. In terms of the effects on NFV, settlement size was linked with forest accessibility through distance to the nearest forest, which was lowest in villages and towns with up to several thousand inhabitants.…”
Section: Discussionmentioning
confidence: 99%
“…Stringent lockdown measures at the beginning of the COVID-19 pandemic (#stay at home) have shown that people cannot stay at home for extended periods of time without negative side effects and therefore the importance of local and neighbourhood open spaces as well as nearby outdoor recreation destinations have become critically important ( Dushkova et al, 2021 ; Kleinschroth & Kowarik, 2020 ; Weinbrenner et al, 2021 ). During COVID-19 pandemic public access to forest areas has been the subject of severe discussions at national and international levels and was changing over pandemic period throughout the world ( Derks et al, 2020 ; Pichlerová et al, 2021 ; Venter et al, 2020 ; Weinbrenner et al, 2021 ). Furthermore, some local restrictions concerning recreational use of specific infrastructure type, such as resting places, picnic spots or related to specific activities were introduced.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%
“…In particular, long-term systematic visitor monitoring techniques, such as the use of pyroelectric sensors, have been useful in capturing actual visitor volumes along recreational trails during the pandemic and in the years before ( Derks et al, 2020 ; Rogowski, 2021 ). Online surveys have also been a commonly used tool in studies of recreational behaviour and use of public open space during pandemic period ( Lopez et al, 2020 ; Pichlerová et al, 2021 ; Rice et al, 2020 ), as direct on-site surveys have not always been possible due to safety distance restrictions.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%
“…During the pandemic, outdoor spaces have provided a significant relief to people under stress (Grima et al, 2020;Lenaerts et al, 2021). Both public and private outdoor spaces have been reported as important (e.g., Lehberger et al 2021), and several papers reveal a significant increase in forest visits both in Europe (Derks et al, 2020;Pichlerová et al, 2021) and overseas (Foley, 2020;Stanturf, Mansuy, 2021). Moreover, the significance of outdoor areas has changed, as forests have acquired a new role not only as "green spaces" but also as "social spaces" where to alleviate the effects of social distancing and to connect with other people (Weinbrenner et al, 2021).…”
Section: Introductionmentioning
confidence: 99%